1975
DOI: 10.1103/physrevlett.34.905
|View full text |Cite
|
Sign up to set email alerts
|

Uniqueness of the Kerr Black Hole

Abstract: The family of Kerr solutions, with \al

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
691
0
8

Year Published

1989
1989
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 876 publications
(710 citation statements)
references
References 5 publications
11
691
0
8
Order By: Relevance
“…In four dimensions, the Carter-Robinson uniqueness theorem [3,5] on the Kerr rotating black hole rests on using the Papapetrou form (1.1) of the metric. We expect therefore similar arguments to be applicable in higher dimensions, although they of course cannot prove any kind of strict uniqueness for five-dimensional rotating black holes due to the existence of rotating black rings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In four dimensions, the Carter-Robinson uniqueness theorem [3,5] on the Kerr rotating black hole rests on using the Papapetrou form (1.1) of the metric. We expect therefore similar arguments to be applicable in higher dimensions, although they of course cannot prove any kind of strict uniqueness for five-dimensional rotating black holes due to the existence of rotating black rings.…”
Section: Discussionmentioning
confidence: 99%
“…We have therefore proven that for any given function z 1 (y 1 , y 2 ) with ( ∂z 1 ∂y 1 , ∂z 1 ∂y 2 ) = (0, 0) we can find a function z 2 (y 1 , y 2 ) such that 5) and so that (z 1 , z 2 ) is a coordinate system on the two-dimensional manifold.…”
Section: Diagonalizing a Two-dimensional Metricmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, only asymptotically the Kerr geometry is relevant for a rotating body. On the other hand when a rotating mass collapses to a 'black hole,' with |a| < M , Robinson [88] showed that the unique stationary solution to the vacuum field equations is the family of Kerr solutions. We will review the powerful Black Hole Uniqueness Theorems in the next section.…”
Section: What Is the Source Of The Kerr Field?mentioning
confidence: 99%
“…Moreover, he showed that the Kerr metric is the only one admitting zero angular momentum. Robinson [88] gave the definitive proof that the Kerr metric, with |a| < M , is the unique stationary black hole solution to the Einstein vacuum field equations.…”
Section: Black Holes Uniqueness Theoremsmentioning
confidence: 99%